Incidental finding of cutaneous meningeal heterotopia in aplasia cutis congenita. (7th April 2016) - Kenyon, Katharine; Zedek, Daniel; Sayed, Christopher
Abstract : Aplasia cutis congenita and cutaneous meningeal heterotopia are both rare congenital conditions that most commonly occur on the scalp and may appear clinically and histologically similar. A subtype of aplasia cutis congenita, membranous aplasia cutis congenita, and cutaneous meningeal heterotopia are both proposed to result from neural tube closure errors. However, neither non‐membranous nor membranous aplasia cutis congenita are known to occur together with cutaneous meningeal heterotopia in the same lesion. We report the incidental finding of cutaneous meningeal heterotopia within a lesion of aplasia cutis congenita.